INSPIRASI KONSEP ELEMEN DASAR KEHIDUPAN DALAM PERANCANGAN INDOOR BIOSFER - Enrico, Enrico (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
The more our society care about the environment and its sustainability, the more thoughts and ideas surface to enhance the efforts for green activities in the cities we live in. The objective of this discussion is to provide alternative solutions that can be applied to improve such activities, especially for indoor environment such as shopping centres and offices where the people inside are subjected only to the use of air-conditioners and not much of natural air circulation. With more natural elements used in an indoor environment, it would certainly offer a fresh look to the interior design and add more values from the aesthetic point of view. This research is based on qualitative descriptive method accompanied with field study, literature study and visual images.